Nuevos registros de insectos escamas (hemiptera: Sternorrhyncha: Coccoidea) para Cuba - Mestre Novoa, N.=700 1 Hodges, G.S.; Veitia Rubio, M.; Cernuda Bonnin, P.; Herrera Oliver, P.
(Es, En)
Ilus., 27 ref.
Keywords: INSECTA; HEMIPTERA; ESPECIES NUEVAS; REGISTRO; CUBA; INSECTOS ESCAMAS